PENGARUH KARAKTERISTIK INDIVIDU DAN KECERDASAN INTELEKTUAL TERHADAP KINERJA KARYAWAN PADA UD DIAN’S RUMAH SONGKET KLUNGKUNG - Sang Ayu Riska Dwiyantari; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Improving the company's performance in facing the challenges of the increasing number of competitors, UD Dian's Rumah Songket manages its human resources through a recruitment process that considers aspects of Individual Characteristics and the level of Intellectual Intelligence. This study aims to determine the effect of Individual Characteristics and Intellectual Intelligence on Employee Performance at UD Dian's Rumah Songket. This research was conducted at UD Dian's Rumah Songket which is located at Jalan Segening X Gelgel Klungkung Bali, with the object of research being Individual Characteristics and Intellectual Intelligence on Employee Performance. The population in this study were 40 employees at UD Dian's Rumah Songket. The sample of this study was determined by the population method, so the number of samples was 40 people. The data analysis technique used is multiple linear regression analysis. In addition, in this study, classical assumption tests were also carried out which included tests of normality, multicollinearity, and heteroscedasticity. The results of this study indicate that individual characteristics have a positive effect on employee performance at UD Dian's Rumah Songket. Intellectual Intelligence has a positive effect on Employee Performance at UD Dian's Rumah Songket.